PEMBELAJARAN KOOPERATIF BERBANTUAN ALAT PERAGA UNTUK MENINGKATKAN PEMAHAMAN MATEMATIKA SISWA - Asmidi, Asmidi (Jurnal Pembelajaran Prospektif, 2019)
This study is aimed to describe cooperative learning assisted by teaching aids that can improve mathematical understanding of 8th grade students of SMP Negeri 1 Sukadana on cube and beam material. This type of research is classroom action research. The steps of cooperative learning assistedby teaching aids that can improve students' mathematical understanding of cube and beam material are: 1) Conveying goals and preparing students, in this phase the teacher gives apperception and conveys the learning objectives, 2) Presenting information, in this phase the teacher explores students'initial abilities and delivering lesson material 3) Organizing students into learning teams, in this phase the teacher organizes students into heterogeneous learning groups based on student grades and sexes 4) Helping teamwork and learning, in this phase the teacher guides students who have difficulty in completing their group assignments.5) Evaluating, in this phase the teacher gives an individual quiz question. 6) Giving recognition or appreciation, in this phase the teacher gives awards to the group that successfully completes the group task well. Students' understanding of cube and beam material after the application of cooperative learning assisted by teaching aids in this study increased from the"good" category to the "very good" category.